Implementation of Google Classroom in Increasing Students' Islamic Religious Education Learning Participation - Neti Utami (Journal of Islamic Pedagogy and Educational Development, 2025)
Background: This study aims to improve student learning outcomes in Islamic Religious Education subjects, especially in grade VII junior high school students. This study is a type of classroom action research which is divided into 2 learning cycles. Method: The study was conducted on grade VII-A students in the first semester (odd) at SMPN 30 Seluma in the 2024/2025 academic year. While the results of the study conducted on 28 students, in the pre-cycle activities the number of students who completed did not reach 25% of the total number of students. Results: In cycle I, students experienced an increase, the number of students who completed increased with a class average of 67.1%. Then in cycle II, there was a high increase compared to the previous cycle, namely students who had reached the KKM with an average class score of 80.2%. Conclusion: This study shows that the application of learning using animation media can provide good stimulus so that it can improve the understanding of grade VII students in Islamic Religious Education subjects related to obligatory prayer teaching materials.